2023
DOI: 10.3390/v15061330
|View full text |Cite
|
Sign up to set email alerts
|

Unique Profile of Proinflammatory Cytokines in Plasma of Drug-Naïve Individuals with Advanced HIV/TB Co-Infection

Abstract: HIV-1 infection is characterized by aberrant immune activation, and infection with M. tuberculosis by an unbalanced production of proinflammatory cytokines. The expression of these cytokines in HIV-1/TB coinfection is still understudied. Here, we aimed to compare the production of proinflammatory cytokines in drug-naive patients coinfected with HIV-1 and M. tuberculosis (HIV/TB) compared to patients with respective monoinfections. Plasma samples of patients with HIV/TB coinfection (n = 36), HIV-1 monoinfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…Here, in agreement with other studies, in patients with HIV/TB co-infection, we detected the decreased production of IFN-γ beyond the levels observed in both HIV and TB monoinfections (p < 0.0001), [85][86][87][88]. Previously, it was shown that low IFN-γ levels differentiated HIV/TB co-infection regarding the severity of clinical manifestations of TB [89]. This was confirmed by the results of this study, in which, in patients with double infection both with and without TB recurrence, a reduced level of IFN-γ has been correlated with a high percentage of severe forms of TB as follows: 48.4% of patients were diagnosed with disseminated TB, and 30.6% with infiltrative TB in the decay phase.…”
Section: Discussionsupporting
confidence: 92%
“…Here, in agreement with other studies, in patients with HIV/TB co-infection, we detected the decreased production of IFN-γ beyond the levels observed in both HIV and TB monoinfections (p < 0.0001), [85][86][87][88]. Previously, it was shown that low IFN-γ levels differentiated HIV/TB co-infection regarding the severity of clinical manifestations of TB [89]. This was confirmed by the results of this study, in which, in patients with double infection both with and without TB recurrence, a reduced level of IFN-γ has been correlated with a high percentage of severe forms of TB as follows: 48.4% of patients were diagnosed with disseminated TB, and 30.6% with infiltrative TB in the decay phase.…”
Section: Discussionsupporting
confidence: 92%
“…Through the respiratory tract, M.tb invades the lungs and induces the immune response in the host dominated by the pro-inflammatory mechanism to relieve, isolate, and kill pathogens [ 27 , 28 ]. IFN-γ is one of the common pro-inflammatory cytokines that play a key role in controlling the M.tb infection through mediating immune response resulting in the activation of macrophages [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing that IFN-γ levels appear to be negatively correlated with disease severity. TB patients co-infection with HIV had much lower IFN-γ levels than those having only TB infection alone [ 27 ]. Our findings also indicate that the IFN-γ level has significantly been reduced in the TB patient’s serum compared to the healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a nonspecific response to pathogens that involves multiple cells, tissues, and organs. While acute inflammation is stopped, chronic inflammation persists, leading to a chronic inflammatory disease characterized by an overproduction of proinflammatory cytokines and recruitment of inflammatory cells (neutrophils and monocytes) to the affected area(s) [ 20 ]. Thus, Mtb and HIV-1 exploit different scenarios of immune hyperactivation/chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the analysis of cytokines expressed during a HIV/TB coinfection may be important for predicting the course of the disease. While some studies have already been focused on the evaluation of the expression profile of IL-33 in hepatic disease during schistosomiasis [ 15 ], hepatitis, malaria [ 16 ], HIV infected patients [ 17 ] and others on tuberculosis [ 18 ], very few studies have been carried out on the expression of IL-33 in HIV/TB coinfection compared to each of the mono infections [ 19 - 20 ]. The goal of this work was to study the expression of IL-33 cytokine in the context of HIV/TB coinfection and to compare to patients with HIV-1 and TB monoinfections.…”
Section: Introductionmentioning
confidence: 99%